An Improved Criterion for Induced Stability of Fixed-Point Digital Filters with Saturation Arithmetic - Priyanka Kokil; Xavier Arockiaraj S (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
This paper establishes a criterion for the induced  stability of fixed-point state-space digital filters with saturation nonlinearities and external interference. The criterion is established in a linear matrix inequality (LMI) setting, and therefore, computationally tractable. The criterion turns out to be an improvement over a previously reported criterion. A comparison of the presented criterion with existing criterion is made. Numerical examples are given to demonstrate the usefulness of the proposed approach.